Tetrastigma diepenhorstii (Miq.) Latiff (Vitaceae), a New Host of Rafflesia tuan-mudae Becc. (Rafflesiaceae) in Borneo - Wan Nuur Fatiha, Wan Zakaria; Aida Shafreena, Ahmad Puad; Connie, Geri; Ramlah, Zainudin; Abdul, Latiff (Hindawi Publishing Corporation, 2016)
Rafflesia tuan-mudae Becc. (Rafflesiaceae) is endemic to Borneo and was recorded from Sarawak and probably Kalimantan. Previous records showed that Tetrastigma rafflesiae (Miq.) Planch. (Vitaceae) is the only host plant for R. tuan-mudae. In this study the host plants were collected each time R. tuan-mudae was observed or collected. Out of 20 Tetrastigma specimens collected infected by R. tuan-mudae, 14 were identified as T. diepenhorstii (Miq.) Latiff while 6 belonged to T. rafflesiae.Therefore, a new host for R. tuan-mudae is recorded and descriptions for each host are presented.